The perceptions of UNIMAS students on issues of ethnic diversity in small (Ad Hoc) group - Azrina, binti Bunsu. (Universiti Malaysia Sarawak, (UNIMAS), 2009)
This study wa conducted to study the perceptions of UNIMAS students on issues of ethnic diversity in small (ad hoc) group. Interview method was used and 9 interviewees whom are UNIMAS diverse students were involved. There has been a mixed up of positive and negative perceptions of being in a diverse group especially in small (ad hoc) group type. There are some findings that correlate with previous research and some are new findings. In addition, the implications of this study to compensation theory and practice, conceptual and methodological limitations and directions for future research are discussed.